Electric vehicles: To what extent are environmentally friendly and cost effective? – Comparative study by european countries. (November 2021) - Costa, C.M.; Barbosa, J.C.; Castro, H.; Gonçalves, R.; Lanceros-Méndez, S.
Abstract: Energy and environmental issue are among the most relevant challenges to be solved in the near future. Electric vehicles (EVs) will play a key role in the solution by positively contribute to these two issues. The growth of the EV market both in Europe and the rest of the World in last years, arose a relevant question: to what extent are electric vehicles eco-friendly and cost effective in comparison with internal combustion engine vehicles (ICEVs)? This work presents a comparative study between battery electric vehicles and ICEVs from different European countries, with special focus on two relevant issues: economic viability and ecological impact. It is shown that in the European Countries, the economical payback is much variable. In other countries, the economic payback can vary between travelled distances of about 2500 km (Portugal) and 335 000 km (Czech Republic). The environmental benefit is reached after relatively low travelled distances, between 30 000 km (Norway) and 190 000 km (Poland), being more evenly distributed when compared to the economical payback. It is also shown how economic and environmental benefits depend on mobility profile, being improved for longer travel distance profiles. It was concluded that the reduction of the price of the EVs is necessary to make them more competitive in the automotive market. Further, it is important to combine both economic and environmental benefits by adopting policies within the European Union to reach a more uniform reality among the different countries, with more levelled prices and revenues (incentives, fees and taxes). Highlights: A comparative study of the economic and environmental viability between different vehicles was carried out. The vehicles types studied were electric (EVs) and internal combustion engine vehicles. It is shown that the economical payback time of EVs is reached in an average of 10 years for European countries. The environmental benefit of electric vehicles is achieved in a relatively time of 3 to 4 years.